THERMODYNAMICS AND NANOSTRUCTURAL MECHANISMS OF PROCESSES OF MELTING AND CRYSTALLIZATION OF METALS - V. Yu. Stetsenko (Литьë и металлургия)
Melting and crystallization of metals are equilibrium thermodynamic processes. As the main structural units of dendrites serve construction nanocrystals which are formed of elementary nanocrystals. The main mechanisms of processes of melting and crystallization of metals are disintegration of dendrites on nanocrystals and formation of dendrites from nanocrystals. On process of crystallization and morphology of dendrites the great influence is exerted by the hardening speed, surface-active elements and the dissolved gases.